Souphanouvong University’s In-Out Documents Management Systems - THIPPHAVANH, phoneouthai; SENGDALA, Sinlapaxay; MEKSAVANH, Bounhome; KEOPASEUTH, Pathoumphone; SITTHIPHONG, Phonesavat; Sililath, Phouthone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
In the era of Digital Transformation 4.0, organizations are adapting to enhance operational efficiency by integrating modern technologies into document management processes. This research aims to: (1) design and develop an Electronic Document Management System (EDMS) for handling incoming and outgoing documents, replacing the traditional paper-based system; (2) investigate the problems of the existing document management system at the university; and (3) assess user satisfaction with the developed system. The system is developed using modern technologies, such as databases and web applications. The research methodology includes requirement analysis, system design, development, testing, evaluation, and system improvement. Research tools include: (1) questionnaires to study problems and user satisfaction, and (2) observation and interviews with relevant staff. The sample group consisted of 12 staff members and personnel who use the incoming–outgoing document management system at Souphanuvong University, selected from each department within the university. Data analysis employed mean and standard deviation to evaluate user satisfaction. The research results show that The developed system can efficiently store, search, and track incoming and outgoing documents, reducing time, costs, and physical storage space while enhancing security; Problems identified in the previous system included document loss, slow searching, and lack of status tracking; Users expressed high satisfaction with the developed system (Mean = 4.4, SD = 0.62) in terms of usability, convenience, and speed in document management.